Marketing Mix Strategies for the Soponyono Corn Cracker SME in the Special Region of Yogyakarta - Sauptika Kancana; Nyoman Tarasanthi Awatari; Nur Istiqomah; Hafreta Intan Alya Musafak; Raden Rara Feodora Remuli Ginting (Green Publisher Indonesia, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) in the snack food sector in the Special Region of Yogyakarta requires business actors to implement effective marketing strategies in order to compete in the increasingly competitive market environment. Emping Corn Soponyono MSME is one of the local businesses utilizing corn as a regional specialty snack product. This study aimed to analyze the influence of the 4P marketing mix consisting of product, price, place, and promotion on consumer purchasing decisions and to determine appropriate business development strategies. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using SWOT analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Quantitative Strategic Planning Matrix (QSPM). The findings revealed that product quality, flavor variations, pricing suitability, product distribution, and promotional activities significantly influenced consumer purchasing decisions. The SWOT analysis indicated that the MSME was positioned in Quadrant II with a conservative strategy approach, while the QSPM analysis showed that structured digital promotion through social media was the top priority strategy. Therefore, the implementation of an appropriate marketing mix combined with well-planned digital promotion can improve competitiveness and enhance consumer purchasing decisions at Emping Jagung Soponyono MSME.